Synthetic Studies on Plakinidines - Komori, Takashi; Yokoshima, Satoshi; Fukuyama, Tohru (Synlett, 2015)
A synthetic route to the pentacyclic core of the plakinidines was developed. Our synthesis features the construction of the fused heterocycles (the A and the E rings) by the formation of carbon–nitrogen bonds using carbonyl functions prior to the late-stage aromatization of the B ring.
Keywords: acridine; alkaloids; aromatization; Dieckmann condensation; Friedländer quinoline synthesis